Electrochemically synthesized H2O2 at industrial-level current densities enabled by in situ fabricated few-layer boron nanosheets - Yuhan Wu; Yuying Zhao; Qixin Yuan; Hao Sun; Ao Wang; Kang Sun; Geoffrey I. N. Waterhouse; Ziyun Wang; Jingjie Wu; Jianchun Jiang; Mengmeng Fan (Nature Communications)
Abstract Carbon nanomaterials show outstanding promise as electrocatalysts for hydrogen peroxide (H2O2) synthesis via the two-electron oxygen reduction reaction. However, carbon-based electrocatalysts that are capable of generating H2O2 at industrial-level current densities (>300 mA cm−2) with high selectivity and long-term stability remain to be discovered. Herein, few-layer boron nanosheets are in-situ introduced into a porous carbon matrix, creating a metal-free electrocatalyst (Bn-C) with H2O2 production rates of industrial relevance in neutral or alkaline media. Bn-C maintained > 95% Faradaic efficiency during a 140-hour test at 300 mA cm−2 and 0.1 V vs. RHE, and delivered a mass activity of 25.1 mol gcatalyst −1 h−1 in 1.0 M Na2SO4 using a flow cell. Theoretical simulations and experimental studies demonstrate that the superior catalytic performance originates from B atoms with adsorbed O atoms in the boron nanosheets. Bn-C outperforms all metal-based and metal-free carbon catalysts reported to date for H2O2 synthesis at industrial-level current densities.